Estimation of Seed Longevity in Onion Seed Lots by a Vigor Test of Radicle Emergence Test in Artificial Ageing Conditions - Ibrahim Demir; Canan Oztokat Kuzucu; Sıtkı Ermis; Nurcan Memis; Neslihan Kadioglu (Horticulturae, 2022)
The study was conducted to test whether a vigor test of a single count of radicle emergence (RE test) would correlate with the storage potential of 10 seed lots of onion (Allium cepa L.) cultivars in artificial storage conditions. The RE test was performed by counting radicle emergence (2 mm) percentage at 80 h after germination was set up at 20 °C. Seed longevity was determined by storage at 75% relative humidity, obtained by saturated NaCl, at 35 °C over 60 days. Twelve seed samples were taken out during ageing, and seed survival curves were constructed based on normal germination percentages conducted at 20 °C for 12 days in the dark. The seed longevity criterion was P50 (time for the viability to fall to 50%), which was determined through probit analysis by using survival curves. Correlation analysis showed that RE counts at 80 h during germination were highly correlated (p < 0.001) with initial seed quality, Ki (R2 = 0.888) and the half-viability period, P50 (R2 = 0.823). Non-aged pre-storage final normal germination percentages of seed lots were also significantly related to longevity (Ki, R2 = 0.808, p < 0.001, P50, R2 = 0.750, p <0.01), while the level of significance was lower. It can be concluded that the RE test can be used as a fast vigor test to estimate the longevity in onion seed lots.